Adverse Environmental Impact: A Consultant's Perspective. (2002) - Wells, Alan W.; Englert, Thomas L.
Abstract : Environmental consultants are in a unique position to address the practical aspects of a working definition of "adverse environmental impact" (AEI) within Section 316(b) of the Clean Water Act. In our work with the electric utility industry, attorneys, and regulatory agencies, we have encountered numerous and sometimes conflicting interpretations as to what constitutes AEI. In our over 30 years of experience, we have applied most of the approaches suggested for addressing this issue, including biostatistical methods, trend analysis, time series methods, conditional mortality rate models, stock-recruitment models, equivalent adult models, and ecosystem models. In our experience, the paradigm most helpful in bringing about agreement among stakeholders is to (1) create a model of operating scenarios, (2) use empirical data from on-site studies to parameterize the model, (3) convert losses by life stage to equivalent adult losses, (4) convert equivalent adult losses to economic value, and (5) compare scenarios on an economic basis.